A Recent Review on Synthesis, Characterization and Activities of Gold Nanoparticles Using Plant Extracts - Koliyote, Sheeja; Shaji, Jessy (Indian Journal of Pharmaceutical Education and Research, 2023)
Despite advances in synthetic medications, medicinal herbs have empowered mankind with a wide range of efficacious medicines to lessen or eliminate illnesses and suffering from diseases. Since the last decade there has been increasing enthusiasm for the synthesis of gold nanoparticles particularly from herbal extract because the method is a one pot process, environment friendly, safe, convenient and can be produced in large scale. Aqueous extract of several parts of herbs have been utilised, like flower, fruit peel, fruit juice, leaf, stem, seed, rhizome for synthesizing gold nanoparticles. Plants contain phytoconstituents such as alkaloids, flavonoids, polysaccharides, phenols, terpenoids and proteins. These secondary metabolites present, serve as capping and reducing agents in plants, increasing the rate of nanoparticle reduction and stabilisation. Change in colour of yellow coloured auric chloride solution used in the synthesis to ruby red or deep purple or magenta confirms the formation of gold nanoparticles. Various techniques such as UV-visible spectroscopy, scanning electron microscopy, fourier transform infrared spectroscopy, transmission electron microscopy, atomic force microscopy, dynamic light scattering, powder X-ray diffraction, energy dispersive spectroscopy and zeta potential are used to characterize nanoparticles of various sizes, shapes, and surface areas. This review's goal is to present an overview of recent developments in herbal extract-assisted gold nanoparticle synthesis, characterization and applications.
Keywords: Plant extract; Gold nanoparticles; Synthesis; Characterization; Activity